PROSPEK USAHA INOVASI PRODUK KAPSUL BAWANG HITAM SEBAGAI SUMBER ANTIOKSIDAN PENANGKAL RADIKAL DALAM MENGHADAPI PANDEMI - Ratih Apri Utami; Anarofida Anarofida; Meihilda Dona Pratiwi; Ajeng Gendis Purborini; Dhea Karunia Putri; Rofiu Sisil Annisa (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
In the era of the Covid-19 pandemic, an immune booster is needed that can maintain a person's immune system to become more immune to the corona virus. Therefore the product "SULANTAM ABS" is present as an immune supplement. "SULANTAM ABS" (Safe, Efficacious, Healthy Black Garlic Capsules) is an innovation from black garlic which is made in capsule form and aims to make it easier for consumers to consume it to be more effective, efficient, and hygienic. The objectives of this program include: 1) Meeting consumer needs as an immune supplement, 2) Increasing public knowledge about the benefits of black garlic, and 3) Creating innovations from black garlic supplement products in capsule form. The method of making “SULANTAM ABS” product includes the stages of fermentation, drying, flouring, and packaging. Sales of this product have been carried out during August to September 2021, the product sold 20 units with a turnover of Rp. 1,100,000, a profit of Rp. 201,000. and BEP Rp. 96,766. This sales method is mainly done online through e-commerce and offline through consignment. Based on these results, that this business is very profitable and beneficial for the community.